terapi, kolase, anak PENGARUH TERAPI BERMAIN KOLASE TERHADAP KONSENTRASI ANAK BERKEBUTUHAN KHUSUS DI SEKOLAH BERBASIS INKLUSI SDN BEDALI 5 KECAMATAN LAWANG KABUPATEN MALANG - Heny Nurmayunita (Jurnal Keperawatan Malang, 2018)
Abstract Indonesia children with special needs (ABK), especially those who have mental, physical or social / emotional interaction abilities, are still marginalized. Most people still see them as people who are troublesome, disruptive, difficult to learn, unproductive, and burden the community. The purpose of this study was to determine the effect of collage play therapy on the concentration of children with special needs in inclusive schools based on Bedali 5 Elementary School, Lawang District, Malang Regency.This study used the Pre Experiment method with One group Pre-post test. The study population was all children with special needs at Bedali 5 Elementary School, Lawang District, Malang Regency. The sample was selected using a purposive sampling technique of 21 students. The variables used in this study were collage play therapy and concentration of children with special needs. The statistical test used is using the T-test. The results showed that before being given treatment almost all students with special needs had sufficient concentration (95.2%), after being given treatment almost all students with special needs had good concentration (90.5%) and there was an influence between the concentration level of children before and after being given treatment at Bedali 5 Lawang Elementary School Malang Regency with a correlation coefficient of 0.703 and a Sig 2 tailed value of 0,000. This research is expected to provide input to schools to modify the design of learning that is more attractive to students so that the concentration of students can increase and children become motivated to learn. Keywords: Therapy to play collage, concentration, children with special needs